Colors - Yenawine, Philip (New York : Museum of Modern Art : Delacorte Press, 1991)
Isolates the artistic element of color, discusses what thoughts and feelings can be conveyed by different colors, and examines how they contribute to a work of art through various examples.
*SLJ*
Kirkus Reviews
2.1
K-3
Keywords: Color -- Juvenile literature; Color in art -- Juvenile literature; Color; Color in art; Art appreciation; Color; Color in art; Art appreciation